DIVERSITY AND DISTRIBUTION OF TREES ON THE FEDERAL UNIVERSITY OF SÃO CARLOS CAMPUS, BRAZIL: IMPLICATIONS FOR CONSERVATION AND MANAGEMENT - Lessi, Bruno Flório; Bataghin, Fernando Antonio; Pires, José Salatiel Rodrigues (Revista da Sociedade Brasileira de Arborização Urbana, 2017)
The diversity and spatial distribution of trees on the Federal University of São Carlos campus were analyzed. Eighty percent of total individuals of studied area were visited and 130 species belonging to 106 genres and 46 families were founded, of which 51 species are native to the region and 79 exotic species. A satisfactory species diversity was found (H'= 3.89) for an urbanized area. Although the study reveals low dominance of species, the results indicate a same species individuals' aggregation, which all species with the highest abundance have an aggregated spatial distribution. The exotic species number present is bigger than the native species number and should be avoided, especially when it comes to potentially invasive exotic species. The analysis of species distribution in the landscape was a great help to identify the same species individuals' aggregation and to direct management activity on these regions, given the pests and diseases emergence.